2013
DOI: 10.1080/1389224x.2013.817343
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Access to Extension Services and Agricultural Productivity

Abstract: This paper contributes new empirical evidence and nuanced analysis on the gender difference in access to extension services and how this translates to observed differences in technology adoption and agricultural productivity. We employ a cross-sectional instrumental-variable regression method using a regionally-representative dataset of more than 7,500 households and 32,000 plots in four major regions in Ethiopia that was collected during the 2010 main season. Results suggest that female heads of households an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
126
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 15 publications
17
126
3
Order By: Relevance
“…As shown in Table 5, from the total farm households (2077 [298 female heads and 1779 male heads]) living in the three villages, only 15.8 percent of female headed farm households are users of the extension service whereas male headed farm households extension service users account for the lion share (70.7 percent). The result is consistent with other studies that observed access to extension services is lower for females as compared with males (Kassa, 2008;World Bank, 2010;Ragasa et al, 2013). Source: Extension workers documented report, 2012.…”
Section: Gender Dimension In Agricultural Extension Servicessupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Table 5, from the total farm households (2077 [298 female heads and 1779 male heads]) living in the three villages, only 15.8 percent of female headed farm households are users of the extension service whereas male headed farm households extension service users account for the lion share (70.7 percent). The result is consistent with other studies that observed access to extension services is lower for females as compared with males (Kassa, 2008;World Bank, 2010;Ragasa et al, 2013). Source: Extension workers documented report, 2012.…”
Section: Gender Dimension In Agricultural Extension Servicessupporting
confidence: 83%
“…Gender equality is an essential component for sustainable economic growth and poverty reduction (FAO, 2010). As a result several literatures have alerted development practitioners to give emphasis for gender-specific constraints faced by poor female farmers (Quisumbing & Pandolfelli, 2010;Kiptot & Franzel, 2012;Ragasa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lukuyu et al (2012) suggest that farmer trainers would normally disseminate simple technologies such as crop varieties compared to complex ones with higher risks such as crop protection, which alludes to the knowledge they have and their confidence to disseminate such information. Lamontagne-Godwin et al (2017); Ragasa et al (2013) on the other hand suggest differences in cropping patterns, and anticipated farmers' ability to access the various technologies or recommended options as the reason for providing different recommendations by trainers. This implies that even with enhanced knowledge and information dissemination approaches, the type of advice given by trainers is largely conditioned by predicted availability, access, and affordability of recommended practices by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…A suitable attention should be dedicated to the active and actual participation of women in the management committees of farmer organizations, in technical training and in water management associations. Real participation allows for dealing with the fair access of women farmers to the extension services for agriculture [86,87]. In addition, "an effective participation of women within technical and agricultural projects can strengthen both their position and decision power within households and farmer and/or water management organizations, as well as improve the women's compliance with rules and maintenance problems" [48].…”
Section: Discussionmentioning
confidence: 99%